Implementation of Character Formation in Learning Moral Beliefs at MTs Ar-Rahmah - Pitrawana Pitrawana (CV Media Inti Teknologi, 2024)
The problem that occurs at MTS Ar-Rahmah is that there are negative behaviors carried out by students such as violating rules during school hours such as students who arrive late, deliberately do not participate in activities while at school. This study aims to find out how to implement the formation of student character in learning the moral creed of MTS Ar-Rahmah. The research method used is to use a qualitative research approach with the type of qualitative descriptive research, namely research that describes or describes the state or status of a phenomenon. The results of this study show that (1) The process of implementing character formation in learning moral beliefs at MTS Ar-Rahmah is the character of honesty, fairness, responsibility, care, and respect. It is implemented by introducing character values to students, motivating students to have these character values and getting used to doing (2) The results of the implementation of character formation in learning moral beliefs at MTS Ar-Rahmah are that students are honest, students have been really honest in carrying out prayers, then do not cheat during learning evaluation, student responsibility has completed the task on time, Peduli like wanting to help his friend to understand the prayer material, Respect like respecting his friend's opinion that is different from his, then jointly discussed to get a conclusion that is in accordance with the material being studied. Therefore, it can be concluded that there is a change in student behavior, especially in the faith and morals of students after implementing the MTS Ar-Rahmah student character building program.